Pelvic denervation procedures for dysmenorrhea. Issue 4 (August 2017) - Ramirez, Christina; Donnellan, Nicole
Abstract : Purpose of review: Chronic pelvic pain and dysmenorrhea are common conditions affecting reproductive-age women. Surgical pelvic denervation procedures may be a treatment option for women with midline dysmenorrhea, in which medical management is declined by the patient, ineffective at managing symptoms, or medically contraindicated. This review describes the surgical techniques and complications associated with pelvic denervation procedures as well as the current evidence for these procedures in women with primary dysmenorrhea and dysmenorrhea secondary to endometriosis. Recent findings: Presacral neurectomy is the preferred pelvic denervation procedure in patients with primary dysmenorrhea and midline chronic pelvic pain associated with endometriosis. In patients with endometriosis presacral neurectomy is a useful adjunct to excision or ablation of all endometrial lesions to improve postoperative pain relief. There is no additional patient benefit of performing combined presacral neurectomy and uterine nerve ablation procedures. Summary: Pelvic denervation procedures can be performed safely and quickly with a low risk of complication if the surgeon is knowledgeable and skilled in operating in the presacral space. Patients should be adequately counseled on expected success rates and potential complications associated with pelvic denervation procedures. Abstract : Supplemental Digital Content is available in the text